2008
DOI: 10.1007/s12134-008-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Social Participation: The Case of Immigrants in Canada

Abstract: The social engagement of Canada's immigrants continues to be the subject of debates. Most studies indicate a lower level of involvement, particularly for recent immigrants. This article investigates the possible causes of this lower participation by analyzing data from the 1998 General Social Survey (GSS), which provides precise measures of two different types of social engagement: volunteering and social participation. Three results stand out. First, formal volunteering and broader social participation do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 37 publications
1
18
0
3
Order By: Relevance
“…Overall, Asian immigrants' socioeconomic characteristics have little influence on their participation in both ethnic and mainstream volunteering. Although this finding is consistent with the existing literature (Couton and Gaudet 2008;Sundeen et al 2009), the mechanism behind it needs further study. …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, Asian immigrants' socioeconomic characteristics have little influence on their participation in both ethnic and mainstream volunteering. Although this finding is consistent with the existing literature (Couton and Gaudet 2008;Sundeen et al 2009), the mechanism behind it needs further study. …”
Section: Resultssupporting
confidence: 92%
“…Research also suggests that having children in general increases an individual's social networks, and therefore increases their civic engagement (Putnam 2000). However, research finds that various life course events including marriage and parenthood have smaller impacts on immigrants' participation in volunteering than on nonimmigrants' volunteering (Couton and Gaudet 2008;Sundeen et al 2009). For the purpose of this study, one's marital status and parental status are controlled in the model.…”
Section: Family Status: Marital Status and Parenthoodmentioning
confidence: 99%
“…A study conducted by Uzar (2007) on Turkish and Arab immigrants in Germany identified factors that hinder immigrants' participation in decision-making activities as: lack of language proficiency (both language of the host country and technical terms used in the planning process); different perceptions of participation; lack of awareness about participation opportunities; considering the content of discussions as not relevant to their lives; not having enough time; and expecting tangible benefits resulting from the participation. Findings of another study (Couton & Gaudet, 2008) showed that social participation is lower among immigrant women compared to men in Canada due to factors such as lack of previous experiences in social participation and decreased social interactions after immigration. In the context of recreational activities, Aizlewood, Bevelander, and Pendakur (2006) indicated that "ethnic minority status, immigrant status, belonging to a minority religion and speaking a non-official language" have negative impacts on the level of people's participation (p. 22).…”
Section: Introductionmentioning
confidence: 97%
“…The level of their social involvement is low for a number of reasons, such as lack of proficiency in Canada's official languages, different educational systems, cultural differences, geographic locations, lack of information, time and material constraints, and difficulty of entering the Canadian labor markets (Couton and Gaudet 2008). Furthermore the discrimination immigrants encounter in their early life in Canada will hinder their social participation and make social integration problematic.…”
Section: Call For Sunday School Movement In Canada In the 21st-centurymentioning
confidence: 99%